Exploring Formative Assessment and Co-Regulation in Kindergarten Through Interviews and Direct Observation - Braund, Heather; DeLuca, Christopher; Panadero, Ernesto; Cheng, Liying (Frontiers in Education, 2021)
Formative assessment practices have been theoretically connected to the development of self-regulation with mounting empirical evidence. Co-regulation is the process whereby a more capable individual (e.g. teacher or peer) attunes the behaviours, emotions, or cognitive processes of an individual (a student) to align with goals or expectations and is being recognized as a strategy for developing self-regulation. Formative assessment practices may facilitate co-regulation, however, much of the literature has focused on older student populations. This phenomenological study explored the relationship between formative assessment and co-regulation in eight Kindergarten classrooms. Eight Kindergarten teachers and four Early Childhood Educators (ECE) completed semi-structured interviews in 2019 during two time periods with each participant completing two interviews. To supplement the interviews, 56 hours of classroom observations were completed in each classroom, totaling 448 hours of observations across eight classrooms. Interviews were audio-recorded and transcribed verbatim. Qualitative data were analyzed thematically. Four themes have emerged: (a) Authentic assessment and self-regulation practices, (b) Feedback as foundational, (c) Formative assessment and co-regulation have shared purposes, and (d) Connections between classroom assessment and co-regulation. Participants described their classroom assessment and self-regulation practices as authentic and natural for students while also providing examples of their interactions with students as a form of co-regulation. Feedback was articulated as foundational to both classroom assessment and co-regulation. Participants illustrated examples of feedback from peers (including through modified peer-assessment). Shared purposes between formative assessment and co-regulation placed students at the centre of the learning process, encouraging agentic behaviours, and scaffolding student thinking. The final theme underlined the need to broaden conceptualizations of assessment in Kindergarten. Findings suggested student agency as the bridge between classroom assessment and co-regulation, and a bidirectional, mutually supportive, relationship between formative assessment and co-regulation.